Prevalence, risk factors and metabolic profile of the non-obese and obese non-alcoholic fatty liver disease in a rural community of South Asia. Issue 1 (29th December 2020) - Rahman, M Masudur; Kibria, Md Golam; Begum, Hasina; Haque, Mazhar; Sultana, Nigar; Akhter, Mahfuza; Rowshon, A H M; Ahmed, Faruqe; Hasan, Mahmud
Abstract : Introduction: Since there is a paucity of data on the epidemiology of the non-alcoholic fatty liver disease (NAFLD), particularly in rural areas in Asia, we undertook such a study among the population of a rural community in Bangladesh with the aims to (1) determine the prevalence of non-obese and obese NAFLD, (2) compare the sociodemographic clinical and metabolic characteristics between non-obese and obese NAFLD subjects, and (3) determine the risk factors of NAFLD and no-nobese NAFLD. Methods: In this door-to-door survey, clinical examination, anthropometric measurements, biochemical tests and ultrasonography were performed on the adult population (≥18 years) of three villages in Bangladesh. Results: Of 1682, 1353 (80.44%) responded. After the exclusion of 48 subjects for alcohol consumption, HBsAg or anti-hepatitis C virus positivity, 1305 ((mean age 41.28±15.10 years, female 908 (69.6%)) were included in the final analysis. On ultrasonography, among the study population, 57 (4.4%) non-obese, 185 (14.2%) obese and, overall, 242 (18.5 %, (male 23.40%, female 16.4%, p=0. 003)) participants had NAFLD. NAFLD was detected in 57/804 (7.1%) of non-obese and 185/501 (36.93%) obese participants. Among the lean subjects, 24/592 (4.1%) had NAFLD. Among NAFLD subjects, 57 (23.55%) were non-obese, and 53 (22%) had raised alanine aminotransferase. On multivariate analysis, age >40 years, male gender, metabolic syndrome (MS), diabetes mellitus (DM), abdominal obesity, hypertension, dyslipidaemia and obesity were found as the risk factors for NAFLD. There were no differences in sociodemographic characteristics, DM, MS, abdominal obesity, hypertension and dyslipidaemia between non-obese and obese NAFLD (all p>0.05). Conclusion: In this community study in Bangladesh, NAFLD was present in 18.5% participants, one-quarter of whom were non-obese. Apart from body mass index, the metabolic profile was comparable between obese and non-obese NAFLD. Public health measures are needed to control and prevent NAFLD and MS and their adverse health consequences.